Relationships between internal and external handcycle training load in people with spinal cord injury training for the handbikebattle - Sonja de Groot; Sven P. Hoekstra; Paul Grandjean Perrenod Comtesse; Ingrid Kouwijzer; Linda J. Valent (Medical Journals Sweden, 2018)
Objective: To establish the relationship between internal and external handcycling training load for monitoring training in people with paraplegia. Design: Observational study. Subjects: Ten people with paraplegia. Methods: All participants performed a graded peak exercise test. Power output and heart rate (HR) were measured and the session rating of perceived exertion (sRPE) was determined during a 12-week training period. Training Stress Score (TSS) was calculated from power output data, and TRaining IMPuls (TRIMP) was determined, based on HR, HRzones and sRPE. Partial correlations (for all training sessions of all participants) and Pearson's correlations (for all training sessions of an individual participant) were performed to determine the relationship between external (TSS) and internal (TRIMPHR, TRIMPHRzones and TRIMPsRPE) training loads. Results: Partial correlations between measures of internal and external loads (r = 0.81-0.85) and correlations between TRIMPsRPE and TRIMP scores based on HR (r = 0.77-0.78) were very large. At the individual level, Pearson's correlations varied from moderate (r=0.48) to nearly perfect (r = 0.99). Conclusion: TRIMPsRPE and TRIMPHR showed very large correlations with external training load, and thus appear appropriate for use in monitoring handcycling training load in people with paraplegia. How-ever, it is recommended that both measures are used in combination, when possible, since some individuals showed weaker relationships.